2010
DOI: 10.1111/j.1399-3062.2009.00469.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the QuantiFERON-TB Gold In-Tube test with the tuberculin skin test for detecting latent tuberculosis infection in hemodialysis patients

Abstract: QFT-G test results were more closely associated with TB risk factors than were positive TST results. Additionally, the QFT-G test was not affected by BCG vaccination. We concluded that QFT-G test is a more useful diagnostic method than TST for detecting LTBI in HD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
31
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 25 publications
6
31
0
Order By: Relevance
“…In our particular setting, the worst correlations between TST and IGRAs were observed in BCG-vaccinated rCt for the tested antigens ( Յ 0.29; see Table S1 in the supplemental material). These data may suggest that the use of PPD leads to TST false-positive results in BCG-vaccinated individuals, which is in accordance with several studies demonstrating that TST positivity was significantly associated with prior BCG vaccination (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), having odds ratios ranging from 3.8 (95% CI, 1.0 to 13.9) (32) to 24.7 (95% CI, 11.7 to 52.5) (34) in various epidemiological contexts. In contrast, the IGRA agreement between the 2 antigens in WBA ( ϭ 0.69 to 0.75) and LSA ( ϭ 0.48 to 0.50) was not significantly affected by vaccination status, demonstrating that the new constructed PstS-1(285-374):CFP10 fusion protein, as well as ESAT-6:CFP10, may not be cross-reactive with the BCG strains used in Brazil.…”
Section: Discussionsupporting
confidence: 90%
“…In our particular setting, the worst correlations between TST and IGRAs were observed in BCG-vaccinated rCt for the tested antigens ( Յ 0.29; see Table S1 in the supplemental material). These data may suggest that the use of PPD leads to TST false-positive results in BCG-vaccinated individuals, which is in accordance with several studies demonstrating that TST positivity was significantly associated with prior BCG vaccination (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), having odds ratios ranging from 3.8 (95% CI, 1.0 to 13.9) (32) to 24.7 (95% CI, 11.7 to 52.5) (34) in various epidemiological contexts. In contrast, the IGRA agreement between the 2 antigens in WBA ( ϭ 0.69 to 0.75) and LSA ( ϭ 0.48 to 0.50) was not significantly affected by vaccination status, demonstrating that the new constructed PstS-1(285-374):CFP10 fusion protein, as well as ESAT-6:CFP10, may not be cross-reactive with the BCG strains used in Brazil.…”
Section: Discussionsupporting
confidence: 90%
“…However, because the rate of positive results with the QFG-IT (or IP-10) test was also high among those who did not have any risk factors for LTBI (47.2% vs. 30.3%), good agreement was not obtained between the presence of LTBI risk factors and the test results. The IGRA-TST agreement in the diagnosis of LTBI is reportedly generally moderate (42,43), and our findings support this.…”
Section: Discussionsupporting
confidence: 81%
“…The same result has been obtained in CRF patients (41,42). Passalent et al reported that IGRA was positive in more than 70% of CRF patients with risk factors for LTBI, while TST gave positive results in roughly 20% (29).…”
Section: Discussionsupporting
confidence: 64%
“…In nine of these, TST positivity was significantly associated with BCG vaccination as an independent predictor in multivariate analysis [47,50,55,62,67,71,72,74,77] with odd ratios ranging between 3.8 (95% CI 1.0-13.9) [50] [35] GOLETTI [36] JAFARI [37] JAFARI [38] KAMPMANN [39] KANG [40] LEE [41] MARKOVA [42] WANG [43] DETJEN [26] DHEDA [34] GOLETTI [36] KAMPMANN [39] KANG [40] MARKOVA [42] odds for test positivity with M. tuberculosis exposure gradients, or using chest radiography lesions as a surrogate of prior exposure, the IGRAs associated better with exposure than the TST, irrespective of the setting's disease burden. Furthermore, there was generally a poor agreement between IGRAs and TST results (for k statistics, see table 3).…”
Section: Ppv For Progressionmentioning
confidence: 99%
“…Four studies were from intermediate-burden countries (South Korea [55], Lithuania [59], Iran [63] and Turkey [72]) and three studies were from high-burden countries (India [56], South Africa [61] and Vietnam [65]). Seven studies were based solely on paediatric cohorts [39,51,54,59,73,75] and three studies [47,57,61] included children in the study population.…”
Section: Ppv For Progressionmentioning
confidence: 99%